Hand phone packages system advisor / Hanafi Muhamad - Hanafi , Muhamad (2004)
The Hand Phone Package System Advisor is web based applications that be develop as an information platform for the hand phone packages to fulfill the need of the consumer and hand phone company to advertise their product nowadays. The main proposed of the system is to guide user to buy hand phone according to what the consumer need like budget, the hand phone brand and the specification. Case based reasoning is one of the Artificial Intelligent methods that we will implement in the system.